Revealing Transcriptome Landscape of Mouse Spermatogonial Cells by Tiling Microarray - Lee, Tin-Lap. (2012)
Spermatogenesis is a highly regulated developmental process by which spermatogonia develop into mature spermatozoa. This process involves many testis- or male germ cell-specific events through tightly regulated gene expression programs. In the past decade the advent of microarray technologies has allowed functional genomic studies of male germ cell development, resulting in the identification of genes governing various processes. A major limitation with conventional gene expression microarray is that there is a bias from gene probe design. The gene probes for expression microarrays are usually represented by a small number probes located at the 3’ end of a transcirpt. Tiling microarrays eliminate such issue by interrogating the genome in an unbiased fashion through probes tiled for the entire genome. These arrays provide a higher genomic resolution and allow identification of novel transcripts. To reveal the complexity of the genomic landscape of developing male germ cells, we applied tiling microarray to evaluate the transcriptome in spermatogonial cells. Over 50% of the mouse and rat genome are expressed during testicular development. More than 47% of transcripts are uncharacterized. The results suggested the transcription machinery in spermaotogonial cells are more complex than previously envisioned.